A avaliação do nível de qualidade de vida na percepção dos servidores técnicos administrativos de uma instituição de ensino superior: estudo de caso - Albuquerque, Valtércio Araújo de (2013)
The Quality of Work Life (QWL) is very important in the organizational context of a company because through it is possible to have the commitment of employees to perform the tasks and consequently reach the desirable objectives for the organization. It may help in the development of conditions that motivate employees, providing a suitable environment for the execution of tasks, facilitating personal development and promoting interaction between the parties. Realizes that it is the subject of interest to many segments as addresses issues directly related to the well-being of people in different situations. The environment chosen for this study was the Federal University of Paraíba - UFPB - Campus I, located in João Pessoa - PB. The study of Quality of Work Life represents an important role for UFPB in order to provide better ways to manage and assist in the fulfillment of its attributions. This dissertation aims to evaluate the level of Quality of Work Life of technical administrative of UFPB - Campus I. The research presented a qualitative and quantitative methodology, characterized by the interpretation of phenomena and assigning meanings inherent in qualitative research associated with the use of resources and statistical techniques to analyze the results, inherent in quantitative research. The dimensions and variables of the research were based on the measurement model of QWL Walton (1974). Accordingly, we considered eight dimensions addressed the essential questions that this study aims to answer with their respective variables, in order to facilitate their interpretation and simplification of the analysis. The research instrument was composed of 27 questions, each corresponding to a no metric variable that was analyzed according to the method of multivariate analysis known as Factor Analysis (FA) using the statistical software SPSS v.20 (Statistical Package for the Social Sciences) and R 3.0.1 software, which have specific packages for this purpose. The results indicated that the level of Quality of Work Life, according to the perception of technical administrative of UFPB was considered good. Social integration and security, job satisfaction, working conditions, fair remuneration; constitutionalism among others, are fundamental elements in organizational environments healthier. Knowing that information is extremely important, this can support decision making to promote the QWL in the studied organization, ensuring servers technical administrative conditions necessary to do their jobs adequately.